In vitro, in vivo, and cellular mechanisms of Astragalus onobrychis L. extract against protoscoleces and hydatid cysts of Echinococcus granulosus - Ghasemian Yadegari, Javad; Khalaf, Amal Khudair; Oladi, Aram; Shahbazi, Ali; Mahmoudvand, Hossein (Frontiers in Pharmacology, 2025)
IntroductionIn this study, we evaluated the in vitro, ex vivo, and in vivo effects of the chloroform extract of Astragalus onobrychis L. (Fabaceae family) (AOCE) on apoptosis induction and DNA damage in protoscoleces and hydatid cysts of Echinococcus granulosus.MethodsThe protoscolicidal properties of AOCE were examined through both in vitro and ex vivo studies on hydatid cyst protoscoleces, utilizing the eosin exclusion assay. Additionally, we evaluated the effects of AOCE on apoptosis induction and DNA damage in the protoscoleces using a colorimetric protease assay and real-time PCR analysis, respectively. The in vivo efficacy was determined by measuring the quantity, dimensions, and mass of hydatid cysts in infected murine subjects.ResultsThe findings indicated that AOCE, particularly at a concentration of 45.0 mg/mL, effectively eliminated protoscoleces of hydatid cysts within a 30-min exposure period. Additionally, AOCE demonstrated prolonged anti-parasitic effects in ex vivo conditions, in contrast to the immediate lethal effects observed in vitro (p < 0.001). AOCE significantly (p < 0.01) induced caspase-3 activation in protoscoleces obtained from hydatid cysts relative to the control normal saline group. Furthermore, the results from Real-time PCR analysis indicated a significant (p < 0.001) upregulation in the expression levels of the EgATM and EgP53 genes following treatment with AOCE. By in vivo, we found that treatment with AOCE mainly at 200 mg/kg significantly (p < 0.001) reduced the number, size, and weight of hydatid cyst relative to the control group treated with normal saline group. Biochemical analysis also demonstrated that administration of AOCE to infected mice, led to a marked improvement and a reduction in serum levels of liver function factors.ConclusionThe results indicated that AOCE exhibits considerable in vitro and ex vivo scolicidal properties against hydatid cyst protoscoleces. Furthermore, the results highlighted AOCE’s capacity to eradicate protoscoleces through the induction of apoptosis and the infliction of DNA damage. Additionally, AOCE demonstrated significant therapeutic efficacy in managing hydatid cysts in murine models. However, further studies are required to clarify the specific mechanisms underlying its action and to assess its efficacy in clinical trials, which may facilitate the application of AOCE in the context of hydatid cyst surgical procedures.